India-Africa Trade Diversification: Analyzing the Shift from Traditional to Non-traditional Partners (2013-2017) - (:unkn) unknown (My University, 2025)
This study investigates the shifting trade dynamics between India and Africa from 2013 to 2017, with a specific focus on the impact of traditional versus non-traditional trade partners on trade diversification. India, which has long maintained robust trade relationships with South Africa, its traditional partner, has increasingly sought to expand its trade with non-traditional African countries such as Angola, Gabon, Madagascar, and Malawi. Also, it is worthwhile to look at her trade with certain economies who have not been major partners where trade is concerned. Furthermore, the recent shifts towards these non-traditional partners have become central to its trade strategy. Using advanced econometric techniques, including Fixed Effects (FE) and Difference-in-Differences (DiD) models, the study evaluates the changing patterns of India's exports and imports over this period, while accounting for time-related factors and partner type. The findings reveal a notable decline in exports to South Africa post-2015, suggesting a shift in India’s export strategies, while imports from South Africa have remained relatively stable, indicating continued reliance on key commodities from this partner. In contrast, trade with non-traditional partners has not shown substantial growth, highlighting the challenges faced by India in diversifying its trade relationships beyond established markets. Despite the limited expansion with these non-traditional partners, the study underscores the importance of diversifying trade as part of India’s broader economic strategy in Africa. By examining the implications of these trends, the paper contributes valuable insights for policymakers aiming to foster stronger and more diversified India-Africa trade relations through targeted policies, capacity-building efforts, and regional economic integration.
Keywords: African Research